Konsep Kebahagian Tertinggi dalam Pemikiran Boethius: Analisis Kritis terhadap Budaya Konsumerisme (Pusat Riset dan Inovasi Nasional, 2026)
Consumerism is an attitude, mindset, and lifestyle that prioritizes superficial desires. It is influenced by the development of globalization, which has had an impact on people’s lives, both in the cultural and technological fields. Currently, consumerism is a trend in society, with people competing to find happiness by purchasing items that suit their desires, and sometimes seeking recognition from others through consumerist behavior. The rapid development of globalization has greatly influenced today’s societal mindset, with people preferring superficial happiness without considering the impact behind it. The birth of consumerism is inseparable from the rapid development of technology, in this case social media. The presence of social media makes it easier for people to access various things, so that consumerism culture thrives because social media has provided various things. This concept is inversely proportional to Boethius’s concept of happiness. Boethius’s concept of happiness is not about superficial or temporary happiness (wealth, pleasure, and recognition from others), but true, eternal happiness. The purpose of this paper is to understand Boethius’s concept of supreme happiness, which will serve as a critique of consumerist culture. This research uses qualitative methods with a literature review approach (research gap), as well as a philosophical analysis of Boethius’s work, specifically regarding supreme happiness. The results indicate that Boethius’s concept of supreme happiness lies not in material wealth, social recognition, or pleasure, but rather in a relationship with the Divine, or transcendence. Therefore, the implication of this research is the need to reorient society’s understanding of true happiness.